(untitled) (Bangladesh Pharmaceutical Journal, 2021)
Plant gums and mucilage have wide applications in pharmaceutical formulations as emulsifying agents. But these are quite costly, therefore there is always the need for cheaper alternatives. In this study, Okra mucilage from Abelmoschus esculentus (L.) Moench pods was used to formulate Spondias mombin L. leaf extract emulsion. The emulsion was assessed for the effect of the mucilage on antioxidant activity of the extract using four standard in vitro assays. Phytochemical screenings of the mucilage as well as physico-chemical and microscopic characterization of the emulsion were also carried out. The mucilage contained carbohydrates, reducing sugars, terpenoids and unsaturated lactones. The pH of the resulting emulsion was 6.88. The size of the oil globules were small with the average size of 4. 8μm. The extract had superior 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging, hydrogen peroxide radical scavenging and ferric ion reducing capacity compared to the emulsion (p ≤ 0.05). In addition, the emulsion had a better metal chelating activity compared to the extract (p ≤ 0.05). Okra mucilage may have reduced the antioxidant activity of the extract suggesting its incongruity in this emulsion formulation. Bangladesh Pharmaceutical Journal 24(1): 17-25, 2021